3. Soft systems methodology: An alternative approach to improve agribusiness supply chain - I Gusti Lanang Parta Tanaya (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2006)
Abstrak Masalah-masalah sosial yang biasanya melibatkan aktifitas manusia sering kali sulit untuk didefinisikan. Soft systems methodology (SSM) menyajikan cara yang efektif dan efisien untuk masalah yang mengandung sifat saling ketergantungan antara proses teknologi dan aktifitas manusia. Rantai pasokan agribisnis salah satu contoh masalah ini. Rantai pasokan agribisnis adalah suatu sistem sosial yang kompleks yang memiliki tujuan pemenuhan permintaan konsumen dari penawaran produsen secara efisien. Pentingnya peran faktor sosial seperti kerjasama, kepercayaan dan hubungan bisnis antara pelaku menjadikan SSM sesusi untuk mencari lebih dalam faktor penentu yang dapat memperbaiki rantai pasokan agribisnis tersebut. Tulisan ini mengungkap suatu penerapan SSM untuk memperbaiki performasi rantai pasokan agribisnis untuk hasil pertanian petani kecil di lahan kering Pulau Lombok, Indonesia. Beberapa kemungkinan penelitian lanjutan dari hasil pemikiran ini juga diungkapkan Abstract Social problems that usually associated with human activity are frequently poorly defined. Soft Systems Methodology (SSM) provides an effective and efficient way to carry out a systems analysis of problems where technological processes and human activities are interdependent. Agribusiness supply chain is one clear example of the problems. Agribusiness supply chains are complex social systems, which have the objective of efficiently matching consumer demand with product supply. The importance of social factors such as cooperation, trust and relationships among actors suggest that SSM has some potential for exploring improvements to agribusiness supply chains. This paper notifies on an application of SSM to improve agribusiness supply chain performance for dryland farming products from small-scale farmers in Lombok, Indonesia. Some possible future research opportunities are also explored.